Influence of Delta Winglets on Improving heat transfer and friction factor characteristics in tubular heat exchanger - Ruengpayungsak, K.; Samruaisin, P.; Kaewkosum, P.; Pingta, S.; Wongcharee, K.; Phila, A.; Eiamsa-Ard, S.; Thapmanee, P. (My University, 2025)
Heat transfer rate and pressure drop characteristics are two critical constraints that substantially influence the advancement of solar air heaters. The thermal efficacy of these systems is significantly improved by factors such as flow configurations, thermal mechanisms, and geometric modifications. The integration of insertion in turbulators is a common method to improve heat transfer efficiency in solar air heaters. This article presents heat transfer and thermal efficiency in a tubular heat exchanger incorporating Delta winglet (DW). The thermal transfer and pressure drop of air as a working fluid in a tube with a constant heat flux were quantified for Reynolds numbers (Re) between 6000 and 20,000. The DW elements were positioned on two tape sides in a configuration with attack angles (θ) of 30°, 45°, and 60°. Delta winglet height ratios (h/D=0.10) and pitch ratios (p/D=0.1) were examined. Data from the current smooth or plain tubes were also analyzed for comparative purposes. According to the experimental results, the tube with this inserted has a much higher Nusselt number (Nu) and friction factor (f) than a plain tube. Both Nu and f increase as θ decrease. The DW enhances Nu and f by approximately 2.51-3.04 times and 5.21-7.16 times, respectively. The maximum TEF of 1.34 is achieved at an attack angle of 30° and a Reynolds number of 6000. The statistical correlations for Nu f and TEF were analysed and demonstrated a strong fit to the observed data, with discrepancies of ±4%, ±5% and ±3%, respectively. This design improves the conservation of energy in heat exchanger tube applications.
Keywords: Delta winglet; Heat transfer enhancement; Nusselt number; thermal enhancement factor